Aplikasi Pengelolaan Data Warga Dan Pelayanan Surat Pengantar Menggunakan Optical Character Recognition - Kurniawan, Nurul Fallah; Sari, Wahyu Purnama; Supriadi, Irwin (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
The advancement of digital technology has driven innovation across various sectors, including government administration. Digitalization of administrative services offers solutions to improve the efficiency and effectiveness of public services, particularly in data management and the issuance of administrative letters. One frequently submitted document is the cover letter. However, conventional systems at the RT/RW level often lead to delays and increase the risk of document loss or damage. To address this issue, this study focuses on designing and implementing an application to manage citizen data and cover letter services more effectively. The application adopts Optical Character Recognition (OCR) technology to extract information from uploaded documents, simplifying the digitization process and accelerating data verification. Additionally, the Search algorithm is applied to improve data search efficiency, thus expediting services and enhancing data management. The system aims to streamline the administrative process at the RT/RW level in Jamika Village, making it more efficient, timely, and transparent. It is also expected to improve accountability and public trust in administrative services, while serving as a reference for developing other digital administrative systems in the government sector.